Material Teknik Berwujud Logam Jenis Baja Pada Industri Otomotif di Indonesia: Kajian Sistematik - Kurnia, Hibarkah; Darsini, Darsini; Rahmawati, Anita; Putri, Nosa Eka; Alhanas, Mohamad Sigit (Jurnal Pelita Teknologi, 2023)
Rapid industrial development has increased the use of metal materials, especially in the manufacturing industry. There are so many types of metal that companies must choose the right material to produce so that the use of the goods is on target and follows its function. The metal industry has an important role because this industry produces the main raw materials for the activities of other industrial sectors, such as machinery and factory equipment, automotive, maritime, and electronic. This study aims to determine how important metal's role is in Indonesia's manufacturing industry. This research method uses the literature review method of 20 articles that have been analyzed. The contribution of this research hopes that the results of this research can be a useful source of information for researchers and practitioners in the field of industrial engineering.